Virtual Mediation in Islamic Religious Civil Cases Soerjono Soekanto Theory of Law Enforcement Perspective - Durrotun Nafisah; Fadil SJ; Khoirul Hidayah (Budapest International Research and Critics University, 2022)
Mediation in the settlement of Islamic civil cases is a stage that should not be missed by the litigants. Basically, mediation is done face-to-face directly in a special room. However, mediation can be done virtually or using virtual communication media. The implementation of virtual mediation can be done using the WhatsApp, Line, or Zoom Meeting applications. According to Soerjono Soekanto, there are several factors that determine law enforcement, namely legal factors, community factors, cultural factors, facilities and facilities factors and legal factors. The implementation of virtual mediation when viewed from the factors described and all that have not been fulfilled, but there are several things that need to be done so that virtual mediation can be carried out smoothly, there must be a special application there must be a source of legal reference that is specifically regulated.